Perangkap Loyalitas Pelanggan: Sebuah Pemahaman Terhadap Noncomplainers Pada Seting Jasa - Titik Desi Harsoyo (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2009)
It has been agreed by practitioners and academicians in marketing area, that there is a strong relationship between customer satisfaction and loyalty. Customer loyalty is a subsequent of customer satisfaction. It means that satisfied customers are more likely to be loyal, or in other words, the loyal customers are the satisfied ones. Due to the uniqueness of service, it is likely more difficult to predict and analyze customer satisfaction and loyalty. Therefore, this paper aims at reminding us to rethink about this relationship in service setting. Are loyal customers always the satisfied ones? Had not they ever been disappointed, even just once, with the service providers performance? If they had, why do they still intend to repurchase service to the same service providers? Exploring noncomplainers will tell us the story behind the scene of the two mysterious variables. It is hoped that this paper will be able to help service providers to improve their performance in order to build pure loyalty and also to provide further insight for future research.